Association between hypoglycaemic glucose variability and autonomic function in type1 diabetes with impaired hypoglycaemia awareness. (July 2022) - Racca, Caterina; Bouman, Emma J.; Van Beers, Cornelis A.J.; Smits, Mark M.; van Raalte, Daniel H.; Serné, Erik H.
Highlights: Impaired awareness of hypoglycaemia (IAH) is a risk factor for severe hypoglycaemia in people with insulin-treated diabetes. Cardiovascular autonomic neuropathy has been associated with an increased risk for severe hypoglycaemia. In patients with IAH, better cardiovascular autonomic function was associated with increased time in hypoglycaemia and hypoglycaemic glucose variability. Patients with a higher percentage time spent in hypoglycaemic had a lower HbA1c and less microvascular complications. Autonomic neuropathy, does not seem to further deteriorate hypoglycaemic risk in patients with IAH. Abstract: Cardiovascular autonomic neuropathy (CAN) is suggested to underlie hypoglycaemic risk in impaired awareness of hypoglycaemia (IAH). We assessed the prevalence of CAN and the association between glucose variability (GV) and cardiovascular autonomic function in patients with type 1 diabetes (T1DM) and IAH. This study is a post-hoc-analysis of results obtained with the IN-CONTROL-trial, designed to assess the effects of continuous glucose monitoring (CGM) on glycaemia. Forty participants (aged 46.4 ± 11.4 years, diabetes duration 29.1 ± 13.5 years, HbA1c 7.5 ± 0.8%(58.2 ± 8.8 mmol/mol)) underwent 2-week blinded CGM measurements to obtain GV indices. Standardized cardiovascular reflex tests were used to determine the presence of CAN. Cardiovascular autonomic function was assessed with heart rate variability (HRV) measures. 14(35%) participants were classified as having CAN. Participants with CAN had lower percentage time spent in hypoglycaemic range and low blood glucose index(LBGI). After correction for confounders, a significant positive association was found between the coefficient of variation (CV) or time spent in hypoglycaemic range and HRV measures SDRR or RMSSD, and between LBGI and RMSSD. In patients with T1DM and IAH, hypoglycaemic parameters were associated with better cardiovascular autonomic function and lower prevalence of CAN. This suggests that autonomic neuropathy does not seem to further deteriorate hypoglycaemic risk in patients with IAH.